If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 = 8x + -1 Reorder the terms: -5 + 4x = 8x + -1 Reorder the terms: -5 + 4x = -1 + 8x Solving -5 + 4x = -1 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -5 + 4x + -8x = -1 + 8x + -8x Combine like terms: 4x + -8x = -4x -5 + -4x = -1 + 8x + -8x Combine like terms: 8x + -8x = 0 -5 + -4x = -1 + 0 -5 + -4x = -1 Add '5' to each side of the equation. -5 + 5 + -4x = -1 + 5 Combine like terms: -5 + 5 = 0 0 + -4x = -1 + 5 -4x = -1 + 5 Combine like terms: -1 + 5 = 4 -4x = 4 Divide each side by '-4'. x = -1 Simplifying x = -1
| (6+w)(4w-1)=0 | | 1/2×10h=35 | | s^2+3s=-16 | | 5x+7=12x+35 | | 6x-7/5x=3 | | 8x-10=8x-10 | | 13x-9=8x-34 | | x^2+6x = 0 | | 7b+7=42 | | 10x-12=4x+48 | | 11x+12=10x+18 | | 2x(5+3)-16= | | 3p/5=9/4 | | 2x(5+3)-4= | | 3/4-x=7 | | p=2*66+2*94 | | 6x^2*2x^2= | | i+-56=-82 | | 5x/14-11x/7= | | 2.5x=85 | | -16x^2+14t+2=0 | | k-13=-5 | | u-14=-46 | | 3s-2t/6*12/9s-3t | | h(x)=x(x+2)-x(2x-1) | | 50/x=.47 | | y+(-10)=-8 | | 2x-8/7x=1 | | 18-4k=-10+10k | | z=8-i | | 22+3x=-2-8x | | 2x-7/2=3 |